The Deformation, Failure Mechanisms, and Stability Control of the Surrounding Rock of Deep Cross-Measure Roadway: A Case Study - Wenzheng Du; Rui Pan; Hongjin Sun (Advances in Civil Engineering)
In view of the difficulty in controlling the surrounding rock stability of deep cross-measure roadways, a deep cross-measure roadway of the Wanfu coal mine, a typical high-stress mine, was monitored on site and analyzed under the original support scheme. The findings show that the degrees of deformation and failure of the cross-measure roadway varied under different working conditions and that the roadway deformation and failure were mainly characterized by a high fragmentation degree and a large failure range of the surrounding rock and the frequent failure of support components. Considering that the different parts of the cross-measure roadway are located in different lithostratigraphic units, establishing a numerical model of the cross-measure roadway under different working conditions; analyzing the deformation pattern of the surrounding rock of the roadway, the plastic range, and the morphological change pattern; and clarifying the deformation and failure mechanisms of the cross-measure roadway based on field monitoring results. On this basis, two types of evaluation indicators, that is, the deformations of the surrounding rock and the plastic ranges in the four typical parts (roof, shoulder, floor, and sidewalls) of the roadway, were selected to rate the stability of the roadway under different working conditions. Grouting reinforcement-based targeted control countermeasures are proposed to improve the surrounding rock stability. Subsequently, numerical analysis and field application of these control countermeasures were carried out to solve the problem of controlling the surrounding rock stability of deep cross-measure roadways.